THE EFFECT OF THE IMPLEMENTATION OF MARKET E-RETRIBUTION AS AN E-MONEY SYSTEM INNOVATION IN BANYUWANGI DISTRICT - Lucky Maharani Safitri (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
This study aims to show the results of an innovation in the development of non-cash payment systems as a form of technological development, so that it can be said that this newness is better than the previous system. The results showed that the existence of an e-money payment method in market retribution was considered very profitable. This innovation was launched by the Banyuwangi Regency Industry, Trade and Mining Service in collaboration with regional banks in Banyuwangi Regency. The research data was collected through observation and documentation. The limitations of this study include: (1) This research was conducted in the second year of the e-retribution market, so it cannot be used to compare further between when using manual and electronic systems